2006
DOI: 10.1111/j.1365-3156.2006.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B seroprevalence in Thailand: 12 years after hepatitis B vaccine integration into the national expanded programme on immunization

Abstract: Summaryobjectives To evaluate the impact of the universal hepatitis B (HB) vaccination programme on the prevalence of hepatitis B surface antigen (HBsAg) carriers and immunity to HB virus infection among children <18 years and to determine the HB seroprevalence in the Thai population.methods We enrolled people in four provinces, including Chiangrai, Udon Thani, Chonburi and Nakhon Si Thammarat to geographically represent populations in the North, Northeast, Center and South of the country respectively. Serolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 23 publications
6
57
2
1
Order By: Relevance
“…However, this may not be the case when comparing between endemic, high-risk and low-risk, non-endemic regions. Long-term follow-up studies are now being completed investigating antibody levels after initial infant vaccination in endemic regions, like Thailand and high-risk regions of Alaska [4,71]. However, these regions generally have slower antibody decay and more persistent levels over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this may not be the case when comparing between endemic, high-risk and low-risk, non-endemic regions. Long-term follow-up studies are now being completed investigating antibody levels after initial infant vaccination in endemic regions, like Thailand and high-risk regions of Alaska [4,71]. However, these regions generally have slower antibody decay and more persistent levels over time.…”
Section: Discussionmentioning
confidence: 99%
“…After follow-up of universal infant vaccination within these regions, prevalence rates of HBsAg within vaccination age cohorts are now 0.7% and almost 0%, respectively [4,6].…”
Section: Global Usementioning
confidence: 99%
See 2 more Smart Citations
“…Data from UNICEF from 2005 indicated that HBV vaccine coverage in infants ranged from 70 to 90% in most Asia-Pacific countries [45]. Unfortunately, the implementation of vaccination programs is reportedly inconsistent and access to these programs remains limited in some countries such as Myanmar, Bangladesh, and India as well as some rural areas, such as remote areas of China, where coverage is only 29% [2,6,13,45,46] (Table 2). Vaccine failure leading to vertical transmission remains a challenge.…”
Section: Prevention Of Mother-to-child Transmissionmentioning
confidence: 99%